Linguistic competence, Communicative Competence and Interactional Competence - Abdulrahman, Nishad Chathamkulam; Ayyash , Emad A. S. Abu- (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
Linguistic competence, communicative competence, and interactional competence have had a profound impact on second language teaching, learning, and testing. Although a substantial number of studies have been conducted on these three competencies, they have not been conflated for discussion in a single study. Adding this piece to the jigsaw, the current paper explores these three competencies in depth. This paper had a twin purpose of 1) providing a historical account of the linguistic, communicative and interactional competences, and 2) reviewing of the literature on them in order to identify gaps, if any, with the intention to propose new research ideas pertaining to the three types of competences. In order to achieve the study aims, an intensive literature survey was conducted. Based on the review of the related research on linguistic, communicative and interactional competencies, this article offers recommendations for effective classroom practice and future research.